Changes in Aquaporin 1, 5 and 9 Gene Expression in the Porcine Oviduct According to Estrous Cycle and Early Pregnancy - Tanski, Damian; Skowronska, Agnieszka; Eliszewski, Maciej; Gromadzinski, Leszek; Kempisty, Bartosz; Skowronski, Mariusz T (International journal of molecular sciences, 2020)
Aquaporins (AQPs) are a group of small, integral membrane proteins which play an important role in fluid homeostasis in the reproductive system. In our previous study, we demonstrated AQP1, 5 and 9 protein expression and localization in the porcine oviduct. The presence of these isoforms could suggest their role in the transport of the ovum to the uterus by influencing the epithelial cells' production of oviductal fluid. The aim of this study was to evaluate the expression of AQP1, AQP5 and AQP9 in the infundibulum, ampulla and isthmus in the porcine oviduct during the estrous cycle (early luteal phase, days 2-4, medium luteal phase, days 10-12, late luteal phase days 14-16, follicular phase days 18-20) and pregnancy (period before implantation, days 14-16 and after the implantation, days 30-32) using the Real-Time PCR technique. As clearly demonstrated for the first time, AQP1, 5, and 9 gene expression is influenced by the estrus cycle and pregnancy. Furthermore, expression of AQPs in the porcine oviduct may provide the physiological medium that sustains and enhances fertilization and early cleavage-stage embryonic development. Overall, our study provides a characterization of oviduct AQPs, increasing our understanding of fluid homeostasis in the porcine oviduct to successfully establish and maintain pregnancy.
Keywords: hypofýza; Embryonic Development; Pituitary Gland; messenger RNA; Oviducts; pregnancy; aquaporins; Aquaporins; těhotenství; Gene Expression Regulation; estrous cycle; oviduct; Estrous Cycle; pig; regulace genové exprese; Swine; ženské pohlaví; RNA, Messenger; zvířata; estrální cyklus; akvaporiny; Pregnancy; vejcovody u zvířat; Aquaporin 1; embryonální vývoj; akvaporin 1; prasata; akvaporin 5; Female; Aquaporin 5; Animals